Internal Medicine : An Illustrated Radiological Guide - Al-Tubaikh, Jarrah Ali (Springer International Publishing : Imprint: Springer, 2017)
This very well-received book, now in its second edition, equips the radiologist with the information needed in order to diagnose internal medicine disorders and their complications from the radiological perspective. It offers an easy-to-consult tool that documents the most common and most important radiological signs of a wide range of diseases, across diverse specialties, with the aid of an excellent gallery of images and illustrations. Compared with the first edition, numerous additions and updates have been made, with coverage of additional disorders and inclusion of many new images. Entirely new chapters focus on occupational medicine and toxicology imaging, chiropractic medicine, and energy and quantum medicine. Internal Medicine - An Illustrated Radiological Guide puts the radiologist in the internal medicine physician's shoes. It teaches radiologists how to think in terms of disease progression and complications, explains where to look for and to image these complications, and identifies the best modalities for reaching a diagnosis. It will also benefit internal medicine physicians by clarifying the help that radiology can offer them and assisting in the choice of investigation for diagnostic confirmation.
Keywords: Medicine.; Radiology.; Internal medicine.; elektronické knihy; electronic books